Gong and Sekafi Dances of Lundayeh in Kemabong, Sabah : a way to understand the nature of Lundayeh - Chong, Lee Suan (2015)
Lundayeh populations are found in the areas of Tenom, Sipitang and Long Pa Sia, along the west coast of Sabah, Malaysia. Lundayeh dance forms and systems have gone through changes and variations since their existence in Borneo. This paper looks into a variety of aspects, including music, costumes, movements, functions and stories of the traditional dances practiced in today’s Lundayeh communities in Kemabong, Sabah. The surviving traditional dances found to have stemmed from the core of Lundayeh cultural, social and religious aspects of life. The study leads to the discovery of the thinking patterns, life philosophies and world perspectives of Lundayeh that are strongly influenced by their religion and ancient culture. Dance music ultimately serves as a tool to understand the nature of Lundayeh people as one of the minor ethnic groups in Malaysia. The understanding of the nature of Lundayeh would further contribute toward sharing and discovering another dimension of human knowledge and wisdom.